PENGUJIAN VALIDITAS DAN RELIABILITAS KONSTRUK INSTRUMEN KREATIVITAS MAHASISWA PADA MODEL COMPUTER ASSISTED INSTRUCTION (CAI) - Aryo Andri Nugroho; Heni Purwati (Jurnal Riset Pembelajaran Matematika, 2019)
This study aims to examine the validity and reliability of the construct of creativity instruments, determine the contribution of aspects and indicators of creativity in measuring the creativity variable and confirm the hypothesized model that is the suitability of the model with data using the Second order confirmatory factor analysis (2nd Order CFA). The population in this study were second semester students of mathematics education at the University of PGRI Semarang with a total sample of 105 students. Samples were taken using non-probability sampling techniques. Data analysis was performed using the Linear Structural Model (LISREL) version 8.8. The results of the analysis indicate that aspects of fluency, flexibility, originality and elaboration, are able to reflect creativity variables positively, validly and significantly which are supported by behavioral indicators of each aspect. The theoretical model of the creativity variable is fit with empirical data. Valid and significant and reliable aspects of creativity to measure student creativity. The most dominant aspect that reflects creativity is the originality aspect and the weakest aspect is flexibility.